Callaghen - L'Amour, Louis (G. K. Hall, 1972)
Callaghen$1 (Bs business is soldiering. For twenty years he$1 (Bd fought all over the world, from China to the deserts of California; now he$1 (Bs a private in the U.S. Cavalry, poorly paid, his enlistment about to run out. He$1 (Bs ready to move on$1! =(Buntil he comes across a startling discovery: a treasure map belonging to a dead lieutenant who may not have been all that he seemed. The map points the way to an underground river of gold$1! =(Bor does it? To find out, Callaghen will have to fight the toughest war of his life: against a fierce Indian warrior, a vindictive commanding officer, and a ruthless gang of outlaws who$1 (Bll turn what may be a river of gold into a river of blood.s
49539
Keywords: Large Print; Soldier